2018
DOI: 10.1590/0037-8682-0411-2017
|View full text |Cite
|
Sign up to set email alerts
|

Using a Chagas disease hospital database: a clinical and epidemiological patient profile

Abstract: Introduction: Chagas disease (CD) prevention and control rely on studies of its distribution, characteristics of individuals affected and mode of transmission. CD data in Brazil are scarce; a retrospective analysis of the clinical characteristics of 80 patients treated at the Clinical Hospital of UNICAMP, Campinas, Brazil, was performed. Methods: Patient data records were analyzed. Results: Thirty percent of the patients probably got infected through vector-borne transmission, 65% came from endemic areas, a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
(17 reference statements)
3
4
0
2
Order By: Relevance
“…Field studies performed between 1960 and the early 2000s reported a progressive increase in the mean age of patients with chronic CD over time, from less than 25 to 45 years 31 - 33 . Studies on the clinical epidemiological profile of patients with chronic CD in urban centers reported that the mean age showed the same increasing trend in the last decades, ranging from 37.7 to 67.5 years 12 , 13 , 15 , 20 - 22 . Studies conducted in nonendemic regions of the Northern Hemisphere, where patients migrated from South America, especially Bolivia and Central America, reported younger patients with chronic CD with a mean age ranging from 28.5 to 47 years 16 - 18 , 34 - 37 , reflecting the lack of CD vectorial transmission control in their countries of origin and that CD vectorial transmission remained active in rural areas.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Field studies performed between 1960 and the early 2000s reported a progressive increase in the mean age of patients with chronic CD over time, from less than 25 to 45 years 31 - 33 . Studies on the clinical epidemiological profile of patients with chronic CD in urban centers reported that the mean age showed the same increasing trend in the last decades, ranging from 37.7 to 67.5 years 12 , 13 , 15 , 20 - 22 . Studies conducted in nonendemic regions of the Northern Hemisphere, where patients migrated from South America, especially Bolivia and Central America, reported younger patients with chronic CD with a mean age ranging from 28.5 to 47 years 16 - 18 , 34 - 37 , reflecting the lack of CD vectorial transmission control in their countries of origin and that CD vectorial transmission remained active in rural areas.…”
Section: Discussionmentioning
confidence: 87%
“…This finding indicates the knowledge deficit regarding CD among these patients, which reinforces why most of them do not consider living with triatomine bugs as a threat to their health 30 . Several studies on transmission mechanisms have also reported the vector route as the primary route of disease transmission 12 , 13 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diante disso, é primordial a intersetorialidade na gestão, para que atuem na determinação social da doença e na busca contínua do enfrentamento às injustiças sociais (14) . Em um estudo realizado em um hospital de São Paulo (28) e outro em Salvador (23) , observou-se que a maioria dos usuários tem familiares com DCH, o que difere do presente estudo, sendo necessário enfatizar a busca ativa dos familiares.…”
Section: Discussionunclassified
“…Em relação às formas clínicas, houve divergência sobre a forma mais prevalente deste estudo (cardíaca), seguida da indeterminada e digestiva, com os dados do Consenso de Chagas e da OMS, em que a metade dos casos são assintomáticos (21) , seguidos de 30% com distúrbios cardíacos e 10% digestivos (1) , e de outro estudo, com predomínio da forma indeterminada (25) . Entretanto outros estudos também apresentam a forma cárdica como sendo a mais prevalente, seguida da indeterminada (22,23,26,28) .…”
Section: Discussionunclassified